Le végétal dans la fabrique urbaine : une lecture de la stratégie angevine au prisme de l’horticulture et du paysage - Hervé Davodeau; Élise Geisler; Sébastien Caillault (Développement Durable et Territoires)
This article aims at analyzing the narrative of the vegetal in Angers between 2014 and 2022 by the public authorities and the actors of the urban development. Our objective is to try to understand if and how the turning point of the sustainable city and the « transitions » renew discourses and actions on nature and landscapes in the city in a territory historically marked by horticulture and vegetal. The method is based on the analysis of planning documents (especially the Landscape Master Plan and the Nature in the City Plan), recent or ongoing urban projects, and interviews with departments in charge of these environmental and green space issues.